Pengaruh Gaya Hidup Instan dan Self Regulated Learning Terhadap Kesiapan Kerja Generasi Z di Kabupaten Tasikmalaya - Riska Resmiyati; Sri Sudiarti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the effect of instant lifestyle and self-regulated learning on the work readiness of Generation Z in Tasikmalaya Regency. The research uses a quantitative approach with a survey method. The population consists of Generation Z, and the sample was determined using the Cochran formula, resulting in 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire measuring instant lifestyle, self-regulated learning, and work readiness. The data were analyzed using multiple linear regression with statistical software. The results indicate that instant lifestyle has a negative and significant effect on work readiness. This means that individuals who tend to adopt an instant lifestyle are less prepared to enter the workforce. Meanwhile, self-regulated learning has a positive effect on work readiness, although partially it is not statistically significant. Simultaneously, both variables significantly influence work readiness